Stromal Expression of Hypoxia Regulated Proteins Is an Adverse Prognostic Factor in Colorectal Carcinomas - Arjen H. G. Cleven; Manon van Engeland; Bradly G. Wouters; Adriaan P. de Bruïne (Cellular Oncology)
Background: Hypoxia modifies the phenotype of tumors in a way that promotes tumor aggressiveness and resistance towards chemotherapy and radiotherapy. However, the expression and influence of hypoxia-regulated proteins on tumor biology are not well characterized in colorectal tumors. We studied the role of protein expression of hypoxia-inducible factor (HIF)-1α, HIF-2α, carbonic anhydrase 9 (CA9) and glucose transporter 1 (GLUT1) in patients with colorectal adenocarcinomas. Methods: Expression of HIF-1α, HIF-2α, CA9 and GLUT1 was quantified by immunohistochemistry in 133 colorectal adenocarcinomas. The expression of hypoxia markers was correlated with clinicopathological variables and overall patient survival. Results: Expression of these hypoxia markers was detected in the epithelial compartment of the tumor cells as well as in tumor-associated stromal cells. Although tumor cells frequently showed expression of one or more of the investigated hypoxia markers, no correlation among these markers or with clinical response was found. However, within the tumor stroma, positive correlations between the hypoxia markers HIF-2α, CA9 and GLUT1 were observed. Furthermore expression of HIF-2α and CA9 in tumor-associated stroma were both associated with a significantly reduced overall survival. In the Cox proportional hazard model, stromal HIF-2α expression was an independent prognostic factor for survival. Conclusion: These observations show, that expression of hypoxia regulated proteins in tumor-associated stromal cells, as opposed to their expression in epithelial tumor cells, is associated with poor outcome in colorectal cancer. This study suggests that tumor hypoxia may influence tumor-associated stromal cells in a way that ultimately contributes to patient prognosis.